Global instability and strategic crisis - Brown, Neville (Routledge advances in international relations and politics ;, 2004)
The author seeks to bring new perspectives to current debates and argues that control of the missile threats cannot be achieved without addressing ecological, economic, social and cultural elements in a stable world order.